Response surface optimisation of germination conditions to improve the accumulation of bioactive compounds and the antioxidant activity in quinoa - Paucar-Menacho, Luz María (2018)
Germination has been proposed as an economic approach to improve the content of bioactive compounds in pseudocereals. In this work, response surface methodology (RSM) was employed to investigate the impact of germination conditions on the phytochemical content and antioxidant activity of quinoa. The use of desirability methodology showed that the optimum conditions to maximise the content of total phenolic content (TPC) and antioxidant activity in sprouted quinoa were 20 °C for 42 h. Sprouts produced under these conditions exhibited increases of 80% and 30% in TPC and antioxidant activity, respectively, compared to un-germinated seeds, and contained high c-aminobutyric acid (GABA) concentration. The nonsignificant lack-of-fit and high determination coefficients obtained confirmed the suitability of the predictive models developed for TPC and antioxidant activity, whilst the one obtained for GABA was not significant (R2 < 0.75) within the conditions studied. Sprouting under optimum conditions enhanced the content of both flavonoid and nonflavonoid compounds, being the increase in flavonoids more pronounced. Kaempferol-O-dirhamnosyl-galactopyranose and quercetin-O-glucuronide were the compounds that experienced the most noticeable increase in quinoa after germination. In conclusion, this study provides useful information on the optimum germination conditions to improve the levels of health-promoting compounds in quinoa.